Effect of siliceous sand volume fraction on the properties of alkali-activated slag mortars - Hajzler, Jan; Bílek, Vlastimil; Kejík, Marek; Kucharczyková, Barbara (IOP Science, 2023)
One of the critical factors affecting the performance of alkali-activated slag (AAS) is the nature and dose of alkali activator. The activator type can play a significant role during the transition from pastes to mortars or concretes. Therefore, three basic sodium activators (water glass, carbonate, and hydroxide) of the same molarity of 4M Na+ were used to prepare AAS-based mortars with different volume fractions of siliceous sand. These were compared by means of workability, mechanical strength, and long-term shrinkage under autogenous conditions. The results were compared to those obtained on pastes with similar workability. Increasing the content of the sand tended rather to decrease the mechanical properties, while greatly decreased autogenous shrinkage. Nevertheless, the most remarkable differences for different activators were observed when comparing the mortars with pastes. The transition from pastes to mortars resulted in the highest reduction in both compressive and flexural strength for sodium hydroxide. The flexural strength of the mortars with sodium water glass and sodium carbonate even increased considerably in presence of sand.

One of the critical factors affecting the performance of alkali-activated slag (AAS) is the nature and dose of alkali activator. The activator type can play a significant role during the transition from pastes to mortars or concretes. Therefore, three basic sodium activators (water glass, carbonate, and hydroxide) of the same molarity of 4M Na+ were used to prepare AAS-based mortars with different volume fractions of siliceous sand. These were compared by means of workability, mechanical strength, and long-term shrinkage under autogenous conditions. The results were compared to those obtained on pastes with similar workability. Increasing the content of the sand tended rather to decrease the mechanical properties, while greatly decreased autogenous shrinkage. Nevertheless, the most remarkable differences for different activators were observed when comparing the mortars with pastes. The transition from pastes to mortars resulted in the highest reduction in both compressive and flexural strength for sodium hydroxide. The flexural strength of the mortars with sodium water glass and sodium carbonate even increased considerably in presence of sand.
Effect of siliceous sand volume fraction on the properties of alkali-activated slag mortars
Keywords: alkali-activated slag; alkali activators; mechanical properties; autogenous shrinkage; alkali-activated slag; alkali activators; mechanical properties; autogenous shrinkage